CRISPR–Mediated Genome Editing and Gene Repression in Scheffersomyces stipitis. Issue 9 (29th July 2018) - Cao, Mingfeng; Gao, Meirong; Ploessl, Deon; Song, Cunjiang; Shao, Zengyi
Abstract : Scheffersomyces stipitis, renowned for its native xylose‐utilizing capacity, has recently demonstrated its potential in producing health‐promoting shikimate pathway derivatives. However, its broader application is hampered by the low transformation efficiency and the lack of genetic engineering tools to enable sophisticated genomic manipulations. S. stipitis employs the predominant non‐homologous end joining (NHEJ) mechanism for repairing DNA double‐strand breaks (DSB), which is less desired due to its incompetence in achieving precise genome editing. Using CRISPR technology, here a ku70 Δ ku80 Δ deficient strain in which homologous recombination (HR)‐based genome editing appeared dominant for the first time in S. stipitis is constructed. To build all essential tools for efficiently manipulating this highly promising nonconventional microbial host, the gene knockdown tool is also established, and repression efficiency is improved by incorporating a transcriptional repressor Mxi1 into the CRISPR‐dCas9 platform. All these results are obtained with the improved transformation efficiency, which is 191‐fold higher than that obtained with the traditional parameters used in yeast transformation. This work paves the way for advancing a new microbial chassis and provides a guideline for developing efficient CRISPR tools in other nonconventional yeasts. Abstract : Scheffersomyces stipitis has recently demonstrated its potential in producing health‐promoting shikimate pathway derivatives, but its broader application requires sophisticated genome manipulations, which is currently hampered by the low transformation efficiency and the dominant non‐homologous end joining (NHEJ) mechanism. By optimizing the transformation protocol and constructing a ku knockout strain, the transformation efficiency is improved by 191‐fold and the homologous recombination (HR)‐based genome editing by fourfold. Together with the previous developed stable episomal plasmid for effective gene overexpression, a completely genetic manipulation tools for ready implementation in S. stipites is built. This work encourages the studies of a broader collection of nonconventional yeasts whose unique potentials have not been thoroughly explored.